The Games Men Play: How Two-Year College Men Use Video Games to Construct Masculinity - Eric Niemi (Adult Education Research Conference, 2015)
Video games are cultural artifacts that promote learning and development. This study sought to examine how male students enrolled at two year institutions of higher education use video games to construct their masculinity. Additionally, it challenges the assumption that video games offer little to no educational benefits and it challenges the stereotypes associated with playing video games.